Nate the Great stalks stupidweed - Sharmat, Marjorie Weinman; Simont, Marc (New York : Bantam Doubleday Dell Books for Young Readers, 1989)
Nate the Great searches for a missing weed after it disappears from a pot on Oliver's porch.
"A Yearling book."
2.0
Keywords: Weeds -- Fiction; Mystery and detective stories; Weeds -- Fiction; Mystery and detective stories